Phosphorus Forms in Sediments of a River-Dominated Estuary - Watson, Sheree J.; Cade-Menun, Barbara J.; Needoba, Joseph A.; Peterson, Tawnya D. (Frontiers in Marine Science, 2018)
Estuaries are biologically productive transition zones between land and sea that play a vital role in transforming, recycling, and sequestering nutrients and organic matter, thus influencing nutrient loading to coastal systems. Yet, the processes involved in phosphorus (P) transformation and cycling among inorganic and organic P forms are poorly known in estuaries. To better understand the potential for P transformation and sequestration, we identified P forms and estimated their contributions to total P in intertidal wetland sediments of a river-dominated estuary (Columbia River, Oregon, USA) using solution 31P nuclear magnetic resonance spectroscopy (P-NMR). Inorganic P forms dominated sediment P extracts throughout the estuary, with orthophosphate accounting for 71–84% of total extracted P. However, biologically-derived inorganic and organic P forms were also detected. Polyphosphates were found in sediment extracts throughout the estuary, contributing as much as 10% of extracted P. Similar to other wetlands, orthophosphate monoesters and diesters made approximately equal contributions (~ 20%) to total extracted P. However, monoesters (e.g., phytate) were more abundant in sedimentary environments characterized by low organic matter content, while diesters (e.g., DNA) were more abundant in sedimentary environments with high organic matter, regardless of salinity. Collectively, the data show strong evidence for P transformation in sediments of a large, river-dominated estuary, which influences its transport to the coastal Pacific Ocean via the expansive Columbia River plume.